Financial Performance Measurement Of With Signaling Theory Review On Automotive Companies Listed In Indonesia Stock Exchange - Yuniningsih Yuniningsih; Nisrina Atika Hasna; Muh Barid Nizarudin Wajdi; Sugeng Widodo (IJEBD (International Journal of Entrepreneurship and Business Development), 2018)
The Abstract The research aims to determine the role of debt variable, corporate size and growth to the high financial performance of a company with the basis of signaling hypothesis. Analysis method used is multiple linear regression. The unit of analysis is automotive companies listed on Indonesia Stock Exchange period of 2012-2016. The results of the classical assumption test indicate that this research is free of multicollinear, heteroscedasticity and autocorrelation. The results indicate that debt results in negative direction and not significant, corporate size has a negative direction and not significant and company growth has a negative direction and significant. The three results are not in accordance with the hypothesis proposed in the study. The present research has limitation that variables used can only explain 14.4% and the rest are explained by other variables beyond this study.